Uncovering Hiroshima in our midst - Abd Razak, Dzulkifli (2010)
LAST week was the 65th anniversary of the world's first nuclear bomb attacks on Hiroshima and Nagasaki. After more than six decades, the terrors inflicted on people in the twin city bombings are still felt today.